Reviewing Rhetoric in the Classical Period – Plato and Aristotle - Sukandi, Syayid Sandi (TELL - US JOURNAL, 2015)
Plato and Aristotle are key figures in the study of rhetoric. Classical period had been known as the era where rhetoric emerged as the influential language existence. Experts on rhetoric had discussed deeply about the history of rhetoric from the classical period up to the renaissance. In this writing, the focus of the discussion is in the classical period. The reviews being discussed in this writing are mainly derived from ongoing discussion on rhetoric.